Allograft for the treatment of traumatic severe bone loss in the lateral femoral condyle: A case report. (December 2018) - Nizegorodcew, Tomasz; Palmieri, Giuseppe; Peruzzi, Marco; Galli, Marco
Abstract: Background: Open articular fractures are an important issue due to their increasing incidence, along with the rise in motorcycle accidents. Oncology experience with allograft in orthopedics may be extended to cases of traumatic bone loss. Clinical case: A 37-year-old man with an open fracture of the distal femur and proximal tibia presented a massive bone loss of the lateral femoral condyle after a motorcycle accident. Following Damage Control Surgery, a considerable lateral femoral condyle allograft was used to restore the joint anatomy. Results: After an intensive rehabilitation program and two subsequent arthroscopic arthrolyses, the patient resumed walking without aids and recovered from stiffness (R.O.M. 0-130°). An MRI performed at median follow-up, revealed a favorable integration of the allograft. Discussion: Allografts are a reasonable reconstructive option for young individuals with massive bone loss. An appropriately sized allograft is essential to restore an acceptable function as seen in the herein case.